2016
DOI: 10.4103/0974-7796.184892
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis, stone composition, meteorology, and seasons in Malta: Is there any connection?

Abstract: Context:The effect of seasons and meteorology on the incidence of nephrolithiasis has been studied in various regions around the globe, but seldom in the Mediterranean.Aims:This retrospective analysis aims at investigating these putative effects in the Maltese Islands, whose climate is typically Mediterranean, followed by a systematic review of the literature.Materials and Methods:Submission rate and chemical composition of all kidney stones after spontaneous passage or surgical removal between January 2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
3
4
0
2
Order By: Relevance
“…In the present study, using humidity and temperature separately in our regression model, we did not find statistical difference among all types of stones concerning such parameters. Although not exactly comparable, our findings corroborated Buttigieg et al 11 , who observed no association between chemical composition and season, and also with a recent study on stone composition within the USA showing very few differences across all states according to climate 18 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, using humidity and temperature separately in our regression model, we did not find statistical difference among all types of stones concerning such parameters. Although not exactly comparable, our findings corroborated Buttigieg et al 11 , who observed no association between chemical composition and season, and also with a recent study on stone composition within the USA showing very few differences across all states according to climate 18 .…”
Section: Discussionsupporting
confidence: 92%
“…climate (including temperature and humidity levels) may account for the increase in urolithiasis across the world. However, there are scarce data investigating their association with kidney stone composition 11 . Brazil, given its continental size and huge coastal extension, possesses five different climates with a large range of temperature and humidity levels as a result of the territorial extension through the tropics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased incidence of nephrolithiasis is strongly associated with race or ethnicity, region of residence [36], association with temperature, various meteorological parameters, climates, and geographical locations [37]. Seasonal changes showed high urinary calcium saturation in males during summer and in females during early winter [38].…”
Section: Patient and Methodsmentioning
confidence: 99%
“…Only 24 articles were eligible under the full-text assessment (figure 1). Of these, 9 studies directly investigated the impact of ambient temperature on urolithiasis using RR (7-9, 14-19), 12 time-series studies evaluated the linear correlation between mean monthly temperature and incidence of urolithiasis (5,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 6 time-series studies estimated the increased RR as mean daily temperature increased to evaluate the non-linear association (28)(29)(30)(31)(32)(33).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%